Achieving Gender Balance in the Boardroom : India vis-a-vis European Countries - Kumar, Naresh; Sudesh (Prabandhan: Indian Journal of Management, 2016)
There has been a lot of debate about women on boards in India over the last couple of years. Many of the European countries introduced legislative quotas to increase the number of women directors. The provisions of New Companies Act, 2013 and SEBI regulations are expected to bring radical changes in the corporate sector, especially for empowerment of women and transparency in corporate compliance mechanism. For the first time in India, women director appointment has being introduced through the legislative provisions. When the whole world is focusing upon women empowerment and female education to be viewed as an asset and investment, the present study was designed to investigate the status of women representation on boards of selected countries and to make a comparison among them as well as with previous years’ data. The study revealed that India is at the last position, having 12.1% representation on boards among the selected sample countries, which is in contrast with top positions secured by Norway (35.1%), followed by Sweden (32.6%), and then by France (32.5%). The situation for women executive directors is not so favourable ; whereas, it is quite better for women as non-executive directors on FTSE-100 and FTSE-250 companies as compared to the year 2010-11. There was a 60.02% and 87.62% positive change in the number of women directors and number of women independent directors on selected Indian companies’ boards from last year’s data.